2014
DOI: 10.4236/ajps.2014.521352
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel RING-Type Ubiquitin E3 Ligase GhRING2 Differentially Expressed in Cotton Fiber

Abstract: The ubiquitin-proteasome proteolysis pathway is responsible for the degradation of abnormal and short-lived proteins to regulate many important biochemical activities in eukaryotes. By employing affymetrix microarray analysis, we have identified a novel ubiquitin ligase E3 gene Gh-RING2 that is differentially expressed between two Gossypium hirsutum lines-Texas Marker-1 (TM-1) and Chromosome Substitution Line CS-B25. The CS-B25 line has chromosome 25 from G. barbadense substituted into TM-1. The complete nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A ubiquitin ligase E3 gene, GhRING2, was identified that is differentially expressed between two G. hirsutum lines, TM-1, and chromosome substitution line CS-B25 (Soma et al, 2014). GhRING2 was highly expressed in elongating cotton fiber, and GUS expression directed by the GhRING2 promoter was found in hypocotyls and young stems of transgenic Arabidopsis plants.…”
Section: The 2010smentioning
confidence: 99%
“…A ubiquitin ligase E3 gene, GhRING2, was identified that is differentially expressed between two G. hirsutum lines, TM-1, and chromosome substitution line CS-B25 (Soma et al, 2014). GhRING2 was highly expressed in elongating cotton fiber, and GUS expression directed by the GhRING2 promoter was found in hypocotyls and young stems of transgenic Arabidopsis plants.…”
Section: The 2010smentioning
confidence: 99%
“…The perception and signaling pathway of endogenous auxin is considered to trigger plant death through auxin herbicides [2,7]. Through the investigation of Arabidopsis thaliana auxin-resistant mutant lines, the auxin receptor and signaling pathways that are essential for the plant perception and specificity of auxin herbicides were discovered, revealing the ligand/receptor system [8]. The TIR1/AFB gene family consists of six receptors: TIR1 and five homologs of AFB [9][10][11].…”
Section: Introductionmentioning
confidence: 99%